The Contribution of Drifting Snow to Cloud Properties and the Atmospheric Radiative Budget Over Antarctica. Issue 22 (11th November 2021) - Hofer, Stefan; Amory, Charles; Kittel, Christoph; Carlsen, Tim; Le Toumelin, Louis; Storelvmo, Trude
Abstract: The Antarctic Ice Sheet experiences perpetual katabatic winds, transporting snow, and moisture from the interior towards the periphery. However, the impacts of Antarctic moisture and drifting snow on cloud structure and surface energy fluxes have not been widely investigated. Here, we use a regional climate model with a newly developed drifting snow scheme to show that accounting for drifting snow notably alters the spatial distribution, vertical structure and radiative effect of clouds over Antarctica. Overall, we find that accounting for drifting snow leads to a greater cloud cover providing an increase of +2.74 Wm −2 in the surface radiative energy budget. Additionally, a comparison with 20 weather stations reveals a 2.17 Wm −2 improvement in representing the radiative energy fluxes. Our results highlight the need to study the impact of drifting snow processes on the future evolution of clouds, the surface energy budget and the vertical atmospheric structure over Antarctica. Plain Language Summary: Antarctica is the continent with the strongest winds on Earth. These winds pick up a lot of snow on their way from the interior towards the ocean, forming drifting snow clouds. Drifting snow clouds can extend over 1, 000 km horizontally and multiple 100 m vertically. Like a normal cloud, they can reflect incoming sunlight like a mirror and trap heat like a blanket. However, most of our climate models don't yet incorporate these drifting snow clouds and therefore might be missing an important part of the Antarctic climate system. In this study, we show that when we account for drifting snow clouds the Antarctic surface receives notably more thermal radiation. Additionally, we also show that we significantly improve our model when we include drifting snow by comparing our outputs to weather station observations over Antarctica. Therefore, we conclude that accurate Antarctic climate projections need to account for drifting snow. Key Points: Accounting for drifting snow over Antarctica leads to a radiative forcing of +2.7 Wm −2 over the grounded ice sheet Accounting for drifting snow increases the cloud cover over Antarctica by 18.6% Drifting snow is an important‐yet in climate models and observations often neglected‐component of the Antarctic surface energy budget